Task demand effects on postural control in older adults - Prioli, Ana Caroline; Cardozo, Aline Steckelberg; Barbosa de Freitas Junior, Paulo; Barela, Jos Angelo (Elsevier B.V., 2006)
The literature shows conflicting results regarding older adults' (OA) postural control performance. Differing task demands amongst scientific studies may contribute to such ambiguous results. Therefore, the purpose of this study was to examine the performance of postural control in older adults and the relationship between visual information and body sway as a function of task demands. Old and young adults (YA) maintained an upright stance on different bases of support (normal, tandem and reduced), both with and without vision, and both with and without room movement. In the more demanding tasks, the older adults displayed greater body sway than the younger adults and older adults were more influenced by the manipulation of the visual information due to the room movement. However, in the normal support condition, the influence of the moving room was similar for the two groups. These results suggest that task demand is an important aspect to consider when examining postural control in older adults. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: postural control; aging; task demand; moving room